Penerapan Sistem Informasi Manajemen Penjualan Pada Mitra AL Snack - Kinanti Putri Prasasti; Lukki Suherman; Tubagus Mochammad Rayhan Fadlurrahman; Indah Purnamasari (Swabumi, 2023)
At this time information systems are urgently needed by all forms of the business and business world. AL Snack is a business that is engaged in distributing packaged snacks and beverages, in the daily operational activities of AL Snack currently still doing manual transaction recording. It currently takes a considerable amount of time to make one sales transaction because the recording is still manually recorded. To solve this problem, a sales information based system was created so that its sales management would be more effective and efficient, this system was created using Waterfall design method so that it was expected to meet the needs of users on AL Snack. The tools used in the development of the system are the use of PHP programming language with the Laravel framework and the use of PostgreSQL databases. The result of this study is a sales management information system that makes AL Snack easier in managing sales such as sales records, goods stock updates, customer data collection, supplier data collection, and sales reports and applying restrictions on access rights to each user